EMPLOYER BRANDING: COMPANY REPUTATION AND ORGANIZATIONAL ATTRACTIVENESS TO ATTRACT TALENTED EMPLOYEES - Rini Safitri; Khusnul Rofida Novianti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Employer branding is a strategy for attracting and retaining exceptional employees with the purpose of differentiating and creating a unique employment experience. In order to find the best talent, the company needs to pay attention to its reputation and maintain organizational attractiveness from its website recruitment to attract talented employees. This study proposed that employer branding and website recruitment mediated the effect of company reputation on to intention to apply for talented employees in Indonesia’s generation Z using 100 respondents. Data was analyzed using partial least square (PLS) software. The result of this study revealed that employer branding has an insignificant effect on intention Meanwhile, company reputation and website recruitment significantly affect the intention to apply for talented employees.